Information Exchange in a Patient-Physician Encounter. A Quantitative Approach - Ridderikhoff, J. (Methods of Information in Medicine, 1993)
The efficiency of data acquisition in a patient-physician encounter was investigated. In a simulation study, in which 60 family physicians and eight internists participated, the patient was replaced by an actor who used a structured set of patient data. The simulation model proved to be quite natural; data acquisition was primarily influenced by the amount of time available. Discerning between overall and diagnostic information, conclusions could be drawn on the effectiveness of data acquisition. Under time pressure, physicians tend to look for broadly defined symptoms rather than for details of the patient’s illness. The collection of patient data then has an inquisitive character, having implications for the quality of clinical judgement. The physician’s capabilities in eliciting relevant information from a patient appear to be of crucial importance for clinical problem-solving. The present study shows that patient-physician interviewing is effective insofar it concerns broad descriptions, but ineffective in eliciting specific data. If interviewing is laborious and time-consuming this may, therefore, affect the kind of information to be collected.
Keywords: General Practice; Patient Interview; Simulation